The Possibility of Traditional Chinese Medicine as Maintenance Therapy for Advanced Nonsmall Cell Lung Cancer. (4th August 2014) - Xu, Weiru; Yang, Guowang; Xu, Yongmei; Zhang, Qing; Fu, Qi; Yu, Jie; Yu, Mingwei; Zhao, Wenshuo; Yang, Zhong; Hu, Fengshan; Han, Dong; Wang, Xiaomin
Abstract : Lung cancer has become the leading cause of cancer deaths, with nonsmall cell lung cancer (NSCLC) accounting for around 80% of lung cancer cases. Chemotherapy is the main conventional therapy for advanced NSCLC. However, the disease control achieved with classical chemotherapy in advanced NSCLC is usually restricted to only a few months. Thus, sustaining the therapeutic effect of first-line chemotherapy is an important problem that requires study. Maintenance therapy is given for patients with advanced NSCLC if three is no tumor progression after four to six cycles of first-line platinum-based chemotherapy. However, selection of appropriate maintenance therapy depends on several factors, while traditional Chinese medicine (TCM) as maintenance therapy is recommended for all kinds of patients. It has been demonstrated that TCM can prolong the survival time, improve the quality of life (QOL), and reduce the side effects for advanced NSCLC. Although the trials we searched about TCM serving as maintenance therapy is only 9 studies, the results indicate TCM can prolong the progression free survival (PFS) and improve the QOL. So it is possible for TCM to be as maintenance therapy for advanced NSCLC. More rigorous trials are required to further verify its efficacy.